Transforming corporate governance: Excellence in human resources and environment in Indonesia - Gaguk Apriyanto; Fajar Supanto; Ilham Z. Salle; Maxion Sumtaky (SA Journal of Human Resource Management)
Orientation: The orientation of this research is how human resources are integrated into good corporate governance practices to achieve sustainability practices. This research also explores the role of accounting in the context of Indonesian political economy in supporting corporate sustainability and accountability.